Improving English for Banking Using Currency Converter Plus Application on the Fifth Semester Students' at Universitas Bhinneka PGRI - Ika Rakhmawati (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2023)
The material available at the university must adapt to the needs of the job market. From the case English for banking became one of the courses in the English study program at Bhinneka PGRI University. This course is held so that students know about banking which includes currency exchange rates in various countries, how to serve customers, words that are often used in banks, etc. the students experience difficulties in this study, especially in determining foreign currency exchange rates. The design of this research is a classroom action research with cycle model since this research is planned to improve the students’ English for Banking Material at the fifth semester of Universitas Bhinneka PGRI using Currency Converter Plus Application. Action research is a form of collective self-reflective enquiry undertaken by participants in social situations in order to improve the rationality and justice of their own social or educational practices, as well as their understanding of those practices and the situations in which the practices are carried out (Carr and Kemmis 1988: 5-6 in Smith, 2007). According to the result of Test Cycle I done in cycle I, it was found that the students who could reach the passing grade were 15 students (83%) and 3 students (17%) were failed. The criteria of success which had been determined was 80% of the students pass the passing grade and the standard value was 80. So, the action in cycle 1 was successful. The suggestion for the students by using Currency Converter Plus Application, the students can know much English For Banking Material and it makes students more active in teaching and learning process, for English lecturer should use Currency Converter Plus Application as alternative way in teaching English For Banking Material and for future researcher as the reference to make a further research.